(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Drug addiction is a burning problem in Bangladesh affecting vast population especially the youths. The spread of multi drug use has aggravated the overall situation affecting our personal, economical and social life, impairing health status, increasing crime and other unwanted risky behaviour. Objective: To find out the socio-economical status of drug addicted young population in Dhaka City. Materials and Methods: This descriptive cross sectional study was performed during August 2016 to December 2016 at five drug addiction treatment and rehabilitation centre in Dhaka. A total of 57 habitual drug addicted young people were selected by purposive and convenient method of sampling. The primary data was collected by repeated visit to centers and face to face interview with addicts and their family members using a pre tested semistructured questionnaire containing both closed and open ended query. Collected data were compiled and analyzed later on. Results: Most 45(78.95%) of the drug addicted young people were male and among them 12(21.05%) belonged to age group 15-17 years. Majority of addicts 46(80.71%) were Muslim. Educational qualification of 16(28.07%) samples was upto primary level, 21(36.84%) upto secondary level. Considering occupation, majority were students 14(24.56%) followed by unemployed 12(21.05%), day labourer 9(15.79%). Thirty five (61.40%) were the lone earning member of their family. Twelve people (21.05%) had monthly income of family below 10,000 taka. Most of the samples (64.91%) stayed in extended type of family. Thirty seven (75.51%) collected money for drug from family members and stealing from house followed by criminal activities 26(53.06%). Majority of the addicts (85.96%) started taking drugs after being influenced by friends. Causes of drug addiction included unemployment 12(21.05%), peer pressure 9(15.79%) and influence of foreign culture 8(14.03%). The commonly used drugs included- Barbiturate/sedatives 32(56.14%), Yaba 28(49.12%), Toluene/aica 22(38.59%). Oral route was the commonest 48(84.21%) followed by Injection 9(15.79%). Commonest place of drug addiction included dance bar/club house 18(31.58%), isolated room/mess 14(24.56%), open field 12(21.05%) and railway/ bus station 9(15.79%). Conclusion: The dangers of drug addiction have been shifted from upper to middle and lower middle class population of our country. Elaborate national plan is needed to motivate young generation for involvement in study and productive activities. Preventive measures for drug smuggling and addiction are needed to be taken with great caution. More drug addiction treatment and rehabilitation centres are required to combat present situation. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 15-20